2022
DOI: 10.3390/buildings12020099
|View full text |Cite
|
Sign up to set email alerts
|

Development of a BIM and IoT-Based Smart Lighting Maintenance System Prototype for Universities’ FM Sector

Abstract: Reactive maintenance (RM) is a core service of the operation and maintenance (O&M) phase, the most prolonged and costly within the building lifecycle. RM is characterised by inefficient asset information and communication management, impacting critical FM problems and users’ experience. Building information modelling (BIM) and Internet of things (IoT) has enabled the development of digital twins, moving facilities management (FM) from a reactive approach towards a predictive one. Although previous studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 71 publications
(118 reference statements)
0
12
0
Order By: Relevance
“…BACS support facility managers with providing real-time monitoring and notifications of defects, enabling faster response and minimising potential hazards (Villa et al, 2022). However, reactive maintenance can be costly as it requires urgent and unexpected repairs or replacement and it disrupts the optimal operation of the building (Fialho et al, 2022).…”
Section: Reactive Proactive and Predictive Maintenancementioning
confidence: 99%
“…BACS support facility managers with providing real-time monitoring and notifications of defects, enabling faster response and minimising potential hazards (Villa et al, 2022). However, reactive maintenance can be costly as it requires urgent and unexpected repairs or replacement and it disrupts the optimal operation of the building (Fialho et al, 2022).…”
Section: Reactive Proactive and Predictive Maintenancementioning
confidence: 99%
“…There are various studies on the integration of BIM and IoT at the operational phase of buildings [16][17][18][19]. Studies either investigated the potential of their integration or demonstrated such integration through prototypes throughout the project lifecycle [20].…”
Section: Related Workmentioning
confidence: 99%
“…Studies either investigated the potential of their integration or demonstrated such integration through prototypes throughout the project lifecycle [20]. Fialho et al [19] demonstrated the application of BIM and IoT prototypes for smart lighting management, which showed the potential for complementing reactive maintenance with predictive insights. Chung et al [21] proposed a process in which virtual reality and open BIM are combined to enable smart facility management systems.…”
Section: Related Workmentioning
confidence: 99%
“…Reverse modeling is a method to obtain 3D spatial model by combining the point cloud data scanned in the project with professional modeling software [17][18][19][20]. According to the different ways of 3D model representation, there are two methods to reconstruct 3D models from point cloud data: one is 3D surface model reconstruction, which mainly involves constructing meshes (triangular meshes, etc.)…”
Section: The Established Bim-based Of Facility Management Systemmentioning
confidence: 99%